Health-Related Quality of Life Among Patients Receiving Home Dialysis Therapies - Stein, PhD, MSW, LCSW, Dodie M.; Welch, PhD, RN, FAAN, Janet L.; Kraus, MD, Michael A.; Slaven, MS, MA, James E. (The Journal of Nephrology Social Work, 2015)
Little is known about the health-related quality of life (HRQOL) of patients receiving daily home hemodialysis (DHHD) or peritoneal dialysis (PD). The purposes of this study are to describe the HRQOL of these patients and examine the effect of some demographic and illness characteristics on HRQOL. A total of 114 patients from a single Midwestern unit were included. Average physical component summary (PCS) scores were lower than the general population. Both DHHD and PD patients perceived themselves as having good mental health with mental component summary (MCS) scores at or above those of the general population. These results suggest that the control and independence provided by home therapies have a positive effect on patients’ outlook on life.